Record‐High Ultrasound‐Sensitive NO Nanogenerators for Cascade Tumor Pyroptosis and Immunotherapy - Yuheng Bao; Yanni Ge; Mengjie Wu; Zhengwei Mao; Juan Ye; Weijun Tong (Advanced Science, 2023)
Abstract Pyroptosis is a pro‐inflammatory cell death that is associated with innate immunity promotion against tumors. Excess nitric oxide (NO)‐triggered nitric stress has potential to induce pyroptosis, but the precise delivery of NO is challenging. Ultrasound (US)‐responsive NO production has dominant priority due to its deep penetration, low side effects, noninvasion, and local activation manner. In this work, US‐sensitive NO donor N‐methyl‐N‐nitrosoaniline (NMA) with thermodynamically favorable structure is selected and loaded into hyaluronic acid (HA)‐modified hollow manganese dioxide nanoparticles (hMnO2 NPs) to fabricate hMnO2@HA@NMA (MHN) nanogenerators (NGs). The obtained NGs have a record‐high NO generation efficiency under US irradiation and can release Mn2+ after targeting the tumor sites. Later on, cascade tumor pyroptosis and cyclic GMP‐AMP synthase‐stimulator of interferon genes (cGAS‐STING)‐based immunotherapy is achieved and tumor growth is effectively inhibited.